(untitled) - Smith, Janice Gorzynski (New York, 2006)
The Smith: Organic Chemistry text brings new life to the organic chemistry world. This heavily reviewed, new text presents information in the form of bulleted lists and tables; with minimal use of text paragraphs. The author saw a great need for stepped out worked examples; incorporated biological, medicinal, and environmental applications; and an art program that has yet to be seen in organic chemistry! A highlight of the art program are the micro-to-macro art pieces helping students to conceptually understand organic chemistry. Smith: Organic Chemistry is the text you need to see before you make your organic chemistry decision.
Keywords: Chemistry, organic